2021
DOI: 10.1021/acs.jafc.0c04735
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on the Protective Effect of Chlorogenic Acid and 3-(3-Hydroxyphenyl) Propionic Acid against Cadmium-Induced Erythrocyte Cytotoxicity: In Vitro and In Vivo Evaluation

Abstract: The metabolism of chlorogenic acid (CGA) through the intestinal tract was studied. As cadmium is a well-known toxic heavy metal, this study was carried out to investigate the comparative protective effect of CGA and its representative intestinal metabolite (3-(3-hydroxyphenyl) propionic acid, HPPA) against Cd-induced erythrocyte cytotoxicity in vitro and in vivo. We found that CGA and its intestinal metabolite appreciably prevented erythrocyte hemolysis, osmotic fragility, and oxidative stress induced by Cd. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 75 publications
(128 reference statements)
0
7
0
Order By: Relevance
“…The 3-(3-hydroxyphenyl)-propionic acid can be produced by Clostridium bacteria (Rechner et al, 2004). Recently study found this microbial metabolite has a strong antioxidative capacity and can prevent Cd-induced biotoxicity (Cheng et al, 2021). The concentrations of 3-hydroxy-3methylglutaric acid, succinic acid and multiple carbohydrates including sorbitol, xylose 1, D-arabitol and lyxose 1 in the BBC and MIX group were lower than CT group.…”
Section: Discussionmentioning
confidence: 93%
“…The 3-(3-hydroxyphenyl)-propionic acid can be produced by Clostridium bacteria (Rechner et al, 2004). Recently study found this microbial metabolite has a strong antioxidative capacity and can prevent Cd-induced biotoxicity (Cheng et al, 2021). The concentrations of 3-hydroxy-3methylglutaric acid, succinic acid and multiple carbohydrates including sorbitol, xylose 1, D-arabitol and lyxose 1 in the BBC and MIX group were lower than CT group.…”
Section: Discussionmentioning
confidence: 93%
“…for 90 days) in three-yellow chickens by inhibiting lipid peroxidation (MDA) via inducing antioxidant defense (SOD, CAT, GST, GPx, and GSH) and modulating the expression of apoptosis proteins Bax, Bcl-2, Cyt C, and caspase 3 and 9 (Shi et al, 2021). Also, CGA protected against Cd-induced toxicity in erythrocytes as it decreased erythrocyte hemolysis, osmotic fragility, and oxidative stress (Cheng et al, 2021). In another study, CGA alleviated Cd-induced oxidative damage and NO and myeloperoxidase induction in the liver and kidneys of rats and inhibited TLR4/MyD88/NF-κB signaling pathway (Ding et al, 2021).…”
Section: Cadmiummentioning
confidence: 99%
“…3-(3-Hydroxyphenyl) Propionate Acid was reported to be capable of altering the mesenchymal stem cell differentiation program and bone cell senescence [21] . 3-(3-Hydroxyphenyl) Propionate Acid had a strong protective ability against Cadmium-induced erythrocyte cytotoxicity [22] . l -carnitine can be effective in protecting against platinum-induced myelosuppression in bone marrow cells and reduce hematological toxicity in gastrointestinal cancer patients who received LFP chemotherapy [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 96%